Police eaudiobook - Nesbo, Jo (Harry Hole, 2013)
INTERNATIONAL BESTSELLER • In this “invigorating must-read” installment ( Newsweek ) of the New York Times bestselling series, Inspector Harry Hole investigates a serial killer targeting Oslo’s police officers. For years, detective Harry Hole has been at the center of every major criminal investigation in Oslo. His brilliant insights and dedication to his job have saved countless lives over the years. But as the killer grows increasingly bold and the media reaction increasingly hysterical, the detective is nowhere to be found. This time, when those he loves and values most are facing terrible danger, Harry is in no position to protect anyone—least of all himself.